(untitled) (European Journal of Education and Psychology, 2020)
Alcohol consumption has become a serious health problem, today, among young people between 14 and 30 years old. The objective of this study was to analyze communication in social networks in relation to alcohol consumption. During the period of time described, a total of 2063 Twitter comments were collected. The results show the different opinions that users, the media, as well as the police or protest groups have about alcohol consumption. Thus, the majority of young people support the consumption of alcohol as a way of having fun, while the police, protest groups and the media show society and specifically young people the consequences of consumption. In conclusion, it should be noted how social networks have become the new way of communicating among young people, which facilitates the exchange of opinions, ideas and information worldwide. Thus, they have made it possible to observe how social networks influence alcohol consumption and prevention, therefore, networks can be used as tools to carry out campaigns and programs for the prevention of alcohol consumption in young people, reducing their intake.